2011
DOI: 10.1259/bjr/34972239
|View full text |Cite
|
Sign up to set email alerts
|

The use of joint-specific and whole-body MRI in osteonecrosis: a study in patients with juvenile systemic lupus erythematosus

Abstract: Objective: This study aimed to estimate the prevalence of osteonecrosis (ON) in juvenile systemic lupus erythematosus (SLE) patients using joint-specific and wholebody MRI; to explore risk factors that are associated with the development of ON; and to evaluate prospectively patients 1 year after initial imaging. Method: Within a 2 year period, we studied 40 juvenile SLE patients (aged 8-18 years) with a history of steroid use of more than 3 months duration. Risk factors including disease activity, corticostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 30 publications
1
33
0
2
Order By: Relevance
“…However, because we used an MRI definition of osteonecrosis that is characterized by the presence of the classic band sign and has been validated by histology correlation [8], we presume the osteonecrotic lesions in our patients are consistent with those reported in the literature. Similarly, after initiation of our study, other studies have emerged confirming the utility of WB-MRI in detecting osteonecrosis in various pediatric disorders, such as juvenile lupus [4], juvenile dermatomyositis [5], and hematologic malignancies [1]. Second, at the time of study onset, osteonecrosis was considered a rare complication of ALL therapy.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…However, because we used an MRI definition of osteonecrosis that is characterized by the presence of the classic band sign and has been validated by histology correlation [8], we presume the osteonecrotic lesions in our patients are consistent with those reported in the literature. Similarly, after initiation of our study, other studies have emerged confirming the utility of WB-MRI in detecting osteonecrosis in various pediatric disorders, such as juvenile lupus [4], juvenile dermatomyositis [5], and hematologic malignancies [1]. Second, at the time of study onset, osteonecrosis was considered a rare complication of ALL therapy.…”
Section: Discussionsupporting
confidence: 65%
“…Whole-body MRI (WB-MRI) is an imaging technique that can analyze the entire skeleton with a single diagnostic test [6,17] and has emerged as the preferred imaging modality for evaluation of patients with suspected osteonecrosis in various disorders [6,9,17]. In patients with juvenile systemic lupus erythematosus and juvenile dermatomyositis [4,5], WB-MRI has confirmed multisite osteonecrosis, exclusively located in the lower limbs. In pediatric patients with hematologic malignancies there is one previous study using WB-MRI, which confirmed osteonecrosis in upper and lower extremities [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elles apparaissent très rapidement après l'introduction du traitement (6 e mois) [56] . Elles apparaissent très rapidement après l'introduction du traitement (6 e mois) [56] .…”
Section: Diagnosticunclassified